2019
DOI: 10.5194/nhess-19-2053-2019
|View full text |Cite
|
Sign up to set email alerts
|

The Floodwater Depth Estimation Tool (FwDET v2.0) for improved remote sensing analysis of coastal flooding

Abstract: Remote sensing analysis is routinely used to map flooding extent either retrospectively or in near-real time. For flood emergency response, remote-sensing-based flood mapping is highly valuable as it can offer continued observational information about the flood extent over large geographical domains. Information about the floodwater depth across the inundated domain is important for damage assessment, rescue, and prioritizing of relief resource allocation, but cannot be readily estimated from remote sensing an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 22 publications
(29 reference statements)
0
27
0
Order By: Relevance
“…Outside the United States, the CREST was coupled with an 1D fully distributed linear reservoir routing scheme and found success over a study in China (Shen et al 2017). The National Water Center led an effort to integrate the WRF-Hydro hydrologic model and the Height Above Nearest Datum (HAND) inundation mapping method into the new National Water Model (NWM; Cohen et al 2018). The HAND method performed a simulation of a 2016 Texas flooding event with good agreement with remote sensing observations and less computation cost (Zhang et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Outside the United States, the CREST was coupled with an 1D fully distributed linear reservoir routing scheme and found success over a study in China (Shen et al 2017). The National Water Center led an effort to integrate the WRF-Hydro hydrologic model and the Height Above Nearest Datum (HAND) inundation mapping method into the new National Water Model (NWM; Cohen et al 2018). The HAND method performed a simulation of a 2016 Texas flooding event with good agreement with remote sensing observations and less computation cost (Zhang et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The Science Toolbox Exploitation Platform (SNAP) Toolkit developed by ESA was applied to derive the high-resolution flood inundation extent from Sentinel-1 SAR (Mcvittie 2019). The Floodwater Depth Estimation Tool (FwDET) developed as part of the National Aeronautics and Space Administration (NASA) Applied Sciences Mid-Atlantic Communities and Areas at Intensive Risk demonstration project was employed to achieve flood inundation depths (Cohen et al , 2019.…”
Section: Satellite-derived Land Cover and Flood Inundation Mapsmentioning
confidence: 99%
“…We believe that estimating inundation depths from an inundation map derived from satellite imageries with an associated digital elevation model will support the model calibration and verification processes in data-scarce and ungauged river basins. However, major limitations include obtaining accurate high-resolution DEMs and dealing with fragmented flood inundation domains (Cohen et al 2019).…”
Section: Hydrodynamic Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Digital elevation models (DEMs) are key input data for physically based modeling and flood hazard mapping either with static bathub projections (Cohen et al, 2019; Poulter & Halpin, 2008; Strauss et al, 2012) or hydrodynamic modeling based on the shallow‐water equations (Bakhtyar et al, 2018; Ferreira et al, 2014; Gallien et al, 2014). Several studies, however, have reported limitations of DEMs to represent terrain features including hydraulically important infrastructure (Gallien et al, 2018; Néelz et al, 2006) and high vertical bias that might triple estimates of global vulnerability to sea level rise and coastal flooding (Kulp & Strauss, 2019).…”
Section: Introductionmentioning
confidence: 99%